Effects of Progesterone Intravaginal Devices on Artificial Insemination, Oestrous Synchronization, Ovulation and Pregnancy Rate in Kedah-Kelantan Cattle - Khor, Chun Siah (2002)
The first experiment was conducted to evaluate the effect of various progestagen treatment methods in term of oestrous synchronization, ovulation and pregnancy rate using controlled internal drug-release (CIDR) device or progesterone-releasing intravaginal device (PRID) with prostaglandin F2ct (PGF2ct) injection on the day of CIDRIPRID removal. Twenty-four non-pregnant Kedah-Kelantan (KK) cows were randomly assigned to two groups: CIDR (n=12); PRID (n=12). Both group were given 12-day synchronization treatment and received an intramuscular injection of 25 mg PGF2ct on the day of device removal. The ovaries of all cows were examined by ultrasonography, using a 5 MHz probe, from one day after CIDR/PRID removal until ovulation. Blood samples were collected for determination of progesterone. The proportion of cows observed in oestrus was significantly higher in the CIDR group than PRID group (91.7% vs 58.3%, P<O.Ol). Pregnancy rate was also significantly higher in CIDR group than PRID group (27.3% vs 14.2%, P<0.05). Results from experiment indicated that CIDR is more efficient than PRID. The second experiment was to evaluate the effect of the length of progestagen treatment (12 day vs 7 day) on oestrous synchronization, ovulation and pregnancy rate using controlled internal drug-release device (CIDR) with PGF2a injection at the end of CIDR treatment. Sixteen adult non-pregnant KK cows were divided into two groups: long-term treated group (n=8); Short-term treated group (n=8), day of CIDR removal. All the cows were undergone transrectal ultrasonography, and blood samples were taken for hormone assay. Until 120 h after CIDR removal, the percentage of cows came into oestrus was significantly higher in long-termtreated group than short-term treated group (87.5%). The pregnancy rate was significantly higher in the short-term treated group than in long-term-treated group (40.0% vs 25.0%, follicle in long-term treated group attained a larger maximum diameter than in short-term treated group (P<0.05). The mean time of ovulation after device removal was 108 h in the short-term treated group and 88 ± 5.06 h in the long-tenn treated group; the length of time required for ovulation between two treatment were significantly different (P<0.05). The result showed that the 7-d CIDR+ PGF2a oestrous synchronization protocol rendered a better fertility in Kedah-Kelantan cows.